(untitled) (International Conference on Education, Psychology and Humanities, 2026)
This article examines the pedagogical foundations of preparing schoolgirls for socio-cultural relations through a synergetic approach. In modern educational systems, the development of girls’ social competence, moral values, communication skills, and cultural awareness has become one of the priority tasks. The synergetic approach serves as an innovative pedagogical mechanism that ensures the integration of personal development, social adaptation, and cultural interaction. The article analyzes the theoretical essence of synergetics, its pedagogical opportunities, and the role of educational institutions in forming socio-cultural competence among female students. Furthermore, effective pedagogical methods, interactive technologies, and collaborative educational environments are discussed as important tools for improving girls’ readiness for socio-cultural relationships.